The Emotional Intelligence of Pharmaceutical Sector Workers in Times of the Covid-19 Pandemic (Management and Connections Journal, 2025)
This study aimed to measure the levels of emotional intelligence among workers in the pharmaceutical sector and understand the influences exerted by the pandemic on the management of emotions of these professionals. A field research was conducted, descriptive and with a qualitative and quantitative approach, with 100 professionals working in the Brazilian pharmaceutical sector. The results demonstrated high levels of emotional intelligence in older age groups and a higher level, among women, in the dimension of assessing others' emotions, impacting how these groups managed their emotions during the pandemic period. In addition, pharmaceutical professionals perceived themselves as more resilient, tolerant, and empathetic during the pandemic, but reported experiencing persistent negative consequences such as the development of anxiety, fear, and depression. It was concluded that emotional intelligence played an important role in maintaining good performance at work and in facing the challenges imposed by the pandemic in personal and professional spheres.
Keywords: emotions; pandemic; work; pharmaceutical